Significance of the palace in a way of kindness in Nahj al-Balaghah (Journal of the College of Basic Education, 2022)
The palace is considered one of the styles rich in structures and rich in connotations. It is an art and a workmanship at the same time, due to its many benefits, the depth of its secrets, and the diversity of its methods. The diversity of his ways and their multiplicity is only a reason for the difference in his significance and the point of his discourse.The ways of limitation are not the same in terms of significance, but there are subtle differences between them, which require contemplation and sharpening of eyesight in order to stand on them and realize the beauty of their charm, because what is easy in other compositions is difficult and difficult with them. And Darbah (), due to the possibility that it is not proven in its rank, or that each of them occurs as a description or adjective, as well as the possibility of defining them according to the grammatical context of the first three methods: (but, negation and exception, and conjunction), and either with